(untitled) (Studia Prawnicze / The Legal Studies, 2010)
Dokonująca się w Polsce reforma prawa cywilnego obejmująca nawet prace nad stworzeniem nowego kodeksu cywilnego poddała niezbędnym zmianom także prawo spadkowe (poszerzono krąg spadkobierców ustawowych o dziadkówspadkodawcy oraz pasierbów). Przemiany wynikły przede wszystkim z potrzeby rewizji założeń nie tylko prawa spadkowego, ale i całego prawa cywilnego, nierozerwalnie związanych ze zmianą ustroju społeczno-gospodarczego. Nadmienić należy, że prawo spadkowe przechodziło ewolucję również w państwach zachodnich. Jednym z takich państw jest Szwajcaria, której kodeks cywilny stałsię wzorcem dla wielu innych ustawodawstw. Z tego też względu warto przyjrzeć się, w jakim kierunku podążały zmiany szwajcarskiego prawa spadkowego. Article Directions Swiss-inheritance law-changes deals with the issues of the wider rights of inheritance law in force in Switzerland. Given that the close ties of Polish law with European law are not without influence on the Polish civil law, including inheritance laws, there is an attempt to analyze the wording of the standards of modern Swiss inheritance law and jurisprudence BGer exegesis in this regard. Not to mention the role of the Swiss Civil Code, which became the model for many other laws, including the Polish legislation. In the era of draft amendments to Polish law of inheritance may have a value of retrospective look at the evolution of a European legal systems. The article is thus an attempt to describe the influence of the most significant revision of choices in Swiss inheritance law (including those relating to the following : equal rights for descendants of heredity, changes in the inheritance by a spouse, inheritance rights of a surviving spouse, registered same-sex partners) at present condition of inheritance law in this country. Analysis of the above solutions allowed to reply the question: what conditions underlay the choice of orders of succession operating in Switzerland, and what conditions determine a wide selection of the class of persons appointed to inherit. The specific practices of legal succession in force in that legal system based on different assumptions of succession (the reserve system, the conventional inheritance) were also taken into account. There were analyzed the following: development of succession rights of selected groups of relatives of the deceased, including above all the deceased spouse and descendants, but also registered partners. Attention was paid to include Such a solution – not found in the Polish legal system – was also indicated, i.e. the accumulation of shares of succession and vested right to use the inheritance by a spouse in force until 1988. Significant practical importance can have also the discussed in the article Erbschleicherei phenomenon concerning all the legal systems, which have had a risk of fraudulent acquisition of inheritance by third parties. The analysis of the descendant rights vested in those connected with the testator only by factual relations, and also detailed arrangements within contractual orders of succession, where a wide choice – after decades of application – is found in Swiss law, may provide a clue to the Polish legislature as to the possible future legislative changes.